Implementation of Business To Customer (B2C) Business Models for IKM (Small and Medium Industry) Registered at the Kediri City Curation House - Permatasari, Distya Ratih (Universitas Nusantara PGRI Kediri, 2023)
Research Aim : The purpose of this research is to find out how the Business To Customer (B2C) business model is implemented by IKMs registered in the development of curated houses in the city of Kediri in an effort to increase sales and develop product potential, as well as materials to contribute to IKMs in upgrading the potential of their products produced. Design/Method/Approach : This study uses descriptive qualitative research with data obtained through observation, interviews, documentation and qualitative data analysis. Sources of informants from this study were taken based on predetermined criteria.